Cultural Dimensions and Educational Technology Adoption in Higher Education: A Mixed-Methods Approach in Developing Countries - Mabina, Alton; Neo Rafifing; Boago Seropola; Kalu Ubi Kalu (COMPETITIVE: Journal of Education, 2025)
This study examines how cultural dimensions influence the acceptance and usage of educational technology in higher education, particularly in developing countries. The research employs a mixed-methods approach, combining quantitative surveys with 250 university students and qualitative interviews with 25 educators and students to explore the role of cultural factors such as power distance, collectivism, uncertainty avoidance, and digital readiness in technology adoption. The findings reveal that collectivist cultures demonstrate higher engagement with collaborative tools, while high power-distance cultures show reliance on authority figures for technology adoption. Additionally, digital literacy gaps and resistance to change hinder widespread implementation. These insights contribute to the theoretical refinement of technology acceptance models by integrating cultural variables and offer practical recommendations for policymakers and educators to design culturally responsive digital literacy programs. The study highlights the need for policies promoting inclusive and equitable access to educational technologies in diverse cultural settings. By addressing cultural barriers, this research advances the discourse on digital education and provides strategies to improve technology integration in higher education.